Uncertainty and Other Forms of Hope: An Environmental Pedagogy - MacDonald, Tanis (Atlantis, 2025)
It’s axiomatic to declare that an environmental pedagogy, especially for women, queer folks, BIPOC people, assault survivors, and anyone who identifies as disabled or vulnerable, is vital to making space for ourselves geographically and psychologically in our workplaces and neighbourhoods. It is equally necessary politically at this stage of late capitalism where the spiked club of use-value is wielded to commodify everything, including our experiences of nature. Trust, risk, and the precarious present have been drawn sharply into pedagogical focus in recent years, exacerbated in the classroom and elsewhere by students’ anxieties about the future that manifest as a withdrawal from the uncertainties of the present moment, including—but not exclusive to—climate anxiety. This article’s examination of living in that shifting “now,” in classroom discussions and in writing assignments, considers the important entanglement of uncertainty and experience as they inform, or even form, hope.